Homosexual Obsessive Compulsive Disorder (HOCD): A Rare Case Report - Bhatia, Manjeet S. (J Clin Diagn Res, 2015)
Homosexual Obsessive Compulsive Disorder (HOCD) is marked by excessive fear of becoming or being homosexual. The subjects often experience intrusive, unwanted mental images of homosexual behaviour. The excessive uncontrolled thoughts/doubts are very distressing and lead to compulsions in form of checking. We present a rare such case who was suffering from HOCD.